Presenting, Promoting, Pitching: And Why You’ll Never Get A Second Crack At A First Impression - Bandler, John (Bandler Corporation, 2017)
Ever struggled with those pesky butterflies before appearing on a stage, or showing up at an unfamiliar event or location? More simply, have you ever had butterflies? No? Then perhaps you’re a psychopath or you’ve never taken a risk. Reasons for your butterflies include fear of failure, and your conviction that there’s no second chance at a first impression. OK. So you think you’re prepared. You’re called. You rise to your feet, you stumble onto the stage. Maybe your microphone or projector doesn’t work. Tough luck. Or you mumble a few opening remarks, maybe swallow your name and affiliation into something unintelligible. By now, your audience has likely made up its mind about you. The rest of your pitch, promotion or presentation simply serves as confirmation of their bias and impressions. As a writer and director of plays as well as a professor and entrepreneur—with experience both in exhibition booths and in mentoring candidates for Three Minute Thesis competitions—I elaborate on effective presentations and pitches: embracing your audience’s needs; gaining trust, those crucial first few seconds, and more. We discuss story, subtext, articulation, theatricality, etiquette, being remembered, ethics, authenticity, admitting setbacks, and how to identify and avoid possible traps and pitfalls.
Slides by John Bandler for a presentation at McMaster University invited by Jonathan Boulanger and Patricia Kousoulas of The Forge, October, 2017. The audience consisted mainly of faculty, staff, graduate students, and young entrepreneurs.
Keywords: subtext; articulation; pitching; theatricality; failure; first impressions; ethics; persuasion; authenticity; gaining trust; risk; Three Minute Thesis